A Unit Plane Edge on-off Slope Algorithm Based Fast LTVR Res-toration Analysis - Praveen Kumar, K.; Venkata Narasimhulu, C.; Satya Prasad, K. (International Journal of Engineering and Technology, 2018)
This research paper presents a Fast LTVR (Localized Total Variation Regularized) method for restoring the degraded images by white noise, while preserving the image edge details in a constructed unit plane edge model through a Unit Plane Edge ON-OFF Slope algorithm. The noisy image contains two details; one with high noise and the other with edge fined details. The edge fine details are restored using ON-OFF Slope algorithm. The denoised image and the edge fine details are used to reconstruct the final restored image. A Unit Plane Edge restoration method is proposed in this research work to estimate the edge-mapping with the fine details. Simulation results of proposed work shows an effective image restoration algorithm comparatively with different filter based restoration methods. Â Â Â
Keywords: Image denoising; filter; ON-OFF; edge; restoration